THE IMPACT OF FBFC-CI ON FUNCTION AND PHYSICAL ACTIVITY. (11th November 2018) - Resnick, B; Galik, E; Vigne, E; Holmes, S D
Abstract: Residents with cognitive impairment are at risk for functional decline and decreased physical activity once they enter nursing homes. Contributors to this decline include cognitive status, age, multiple comorbidities, pain, behavioral symptoms (depression, apathy and aggression) and environmental factors (tethering patients with restraints, the use of alarms, restrictive positioning, limited space and unsafe areas). Twelve settings were randomized to FBFC-CI or education-only and 336 residents included. The residents were 82 (SD=10) years of age, mostly female (n=242, 72%), and white (n= 199, 59%) with a mean Mini Mental State Exam score of 7.8 (SD=5.06). Exposure to FBFC-CI resulted in increased time in physical activity based on actigraphy and subjective reporting of activity. There was no change in function or chair rise. Increasing physical activity via exposure to FBFC-CI has the potential to help with overall health status and quality of life of residents with dementia.